Vulnerability assessment of Southwestern Black Sea - Gormus, Tahsin; Ayat, Berna (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2020)
Climate change-driven impacts such as variation in storminess and sea level rise are affecting coastal areas directly. Determination of coastal vulnerability regarding these effects is very important for planning purposes. In this study, coastal vulnerability of South-Western Black Sea is examined. Physical and social properties of the area have been considered for this purpose. Variables effecting the vulnerability determined as: geomorphology, coastal slope, shoreline change, wave height, mean beach width, sea level rise, population density and land use. Coastal Vulnerability Index (CVI) is used to produce vulnerability map of the study area. Results revealed that highly vulnerable areas are Kiyikoy, Yalikoy, Karaburun, Kilyos, Riva, Sahilkoy, Sile, Agva and Kefken. The least vulnerable areas are located on the coasts lying between Eregli-Zonguldak.
Keywords: Coastal vulnerability index; Black Sea; climate change; geographic information systems; remote sensing; LEVEL RISE; INDEX; INDIA; COAST; Engineering